The Experience of Nursing Care Patient with ECG Letal in Intensive Care Unit Sekarwangi Hospital - Budi Rustandi; Rizky Gumilang Pahlawan; Reni Yuliana (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2022)
Aims: Nurses are required to provide assistance to patients with an accurate Lethal ECG description and maintain their professionalism as a nursing care provider. In carrying out nursing care in the ICU room for patients with lethal ECG, there are many factors that influence the quality of care. Objective: Toexplore the experience of nurses care patients with lethal EKG in the ICU,SekarwangiHospital. Method: This research is a qualitative research with a phenomenological design. The participants selection used purposive sampling technique with 6 nurse. Data obtained through in- depth interviews and analyzed using the Colaizy technique. Results: This studyresulted in 5 themes, namely 1) Nursing Soft Skill , 2) Primary care for Lethal'sECGPatient,3)CollaborationNursingsTeam.4).Hemodynamicstatus,5)Psychological nusring respons. Conclusion: Nurses need to understand their roleas providers of nursing care. Nurses' knowledge needs to be improved so that theimplementation of nursing care can be more optimal. Suggestion This study isexpected to provide an overview and strategy incarrying out nursing care topatients with a lethal ECG description for nurses in the ICU so that nursing carecanbecarried outoptimally.